Evaluasi Implementasi Etika dan Profesionalisme Pegawai dalam Meningkatkan Kualitas Pelayanan TU SMPN 35 Medan - Febriani Br Purba, Yola; Nur Melinda Pradipti Winera; Addina Olivia Saragih; Fitri Yani Nur Fatimah Ritonga (Prodi Pendidikan Administrasi Perkantoran UNIMED, 2025)
Abstract: This study aims to evaluate the implementation of ethics and professionalism among administrative staff at SMP Negeri 35 Medan and analyze its impact on the quality of administrative services. The method used is qualitative phenomenology with three samples of administrative staff whose data was collected through interviews, observation, and documentation, then analyzed thematically. The results of the study indicate that work ethics (discipline, responsibility) and professionalism (competence, discipline) have been consistently applied, which correlates positively with high service quality (reliability, responsiveness) based on the SERVQUAL dimensions. The conclusion of the study confirms that the quality of administrative services is largely determined by the consistency of employee ethics and professionalism. It is recommended that ethical values and professionalism training be strengthened periodically, and that the service system be improved (e.g., digital queuing system). The implication of this study is to provide practical guidance for school management in improving the quality of public services through human resource development. Keyword: Work Ethics; Work Professionalism; Service Quality; Administration.